STUDY OF REGIONAL DRAINAGE CHANNEL CAPACITY AT ALOON-ALOON PONOROGO REGENCY - I Wayan Mundra; Endro Yuwono; Nenny Roostrianawaty; Dodik Prabowo (Journal Innovation of Civil Engineering (JICE), 2021)
The rate of population growth in urban areas is increasing year by year, so that changes in land use will accompany it and have an impact on reducing catchment areas. One of the problems that arise is flooding or inundation. In addition to providing inadequate catchment areas, the existing urban drainage system often does not function optimally with various technical and non-technical problems. One of the urban areas experiencing a similar situation is Ponorogo City, Ponorogo Regency. In some areas of the city, there are still frequent flooding/inundation. For example, in the Ponorogo Regency Government Center, especially around Aloon City. This problem is the background of this study. The results of the study show that the planned flood discharge with a return period of 10 years, which was analyzed based on the modified Rational method, was 0.899 m3/s. Based on data from observations of the existing drainage system, the channel capacity analyzed by the Maning method is only 0.471 m3/sec. Thus the channel capacity needs to be increased. By widening the rectangular base of the channel from 1 m wide to 1.50 m, the channel capacity becomes 0.925 m3/s, so that it can serve according to the planned flood discharge. In addition to increasing the channel capacity, based on observations in the field, it is also necessary to immediately carry out maintenance and repair work on the existing drainage system, so that the function of the channel can be optimal. It is necessary to study the plan to construct infiltration wells in the study area.